Agricultural policy reforms: Roles of markets and states in China and India - Lele, Uma (Glob Food Sec, 2020)
Market reforms have been given much of the credit for China's spectacular growth performance. This paper looks at China's reform process systematically, along with India's, and argues that the Chinese state has played a key role in transforming China into a modern economic state, deploying unlimited supplies of labor and combining it with a variety of initiatives in a pragmatic, nonideological way to promote public and private investment and create productive employment in agricultural, manufacturing, and service sectors. In contrast, India's reforms have been sporadic and are still a work in progress. The record-breaking expansion of China's financial system in fostering investments was initially overlooked, but has attracted considerable attention in recent years. Is China unique, or are lessons from the Chinese experience for public policy and its sequencing transferrable to agricultural and structural transformation in countries lagging behind, including India?